2010
DOI: 10.1021/ac1019842
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mainstream and Sidestream Cigarette Smoke Particulate Matter by Laser Desorption Mass Spectrometry

Abstract: Laser desorption ionization Fourier transform ion cyclotron resonance mass spectrometry (LDI-FTICRMS) was used to investigate particulate matter (PM) associated with mainstream (MSS) and sidestream cigarette smokes (SSS). The high mass resolution and the high mass measurement accuracy allowed a molecular formula for each detected signal in the 150-500 m/z range to be assigned. The high number of peaks observed in mass spectra required additional data processing to extract information. In this context, Kendrick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
(69 reference statements)
3
27
0
Order By: Relevance
“…11,12 Further the current study indicated that female adolescents are more likely exposed to SHS at home than male adolescents are, which is consistent with reviewed study conducted in Iraq. 10 This might be explained by the cultural and traditional background of the country, at which females spend more of their life time at home and usually responsible for the activities inside their home.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…11,12 Further the current study indicated that female adolescents are more likely exposed to SHS at home than male adolescents are, which is consistent with reviewed study conducted in Iraq. 10 This might be explained by the cultural and traditional background of the country, at which females spend more of their life time at home and usually responsible for the activities inside their home.…”
Section: Discussionsupporting
confidence: 90%
“…These employees, who are often women, are exposed not only involuntarily, but also at high level. 12 The …”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the latest evidence has shown that the chemical compounds observed in sidestream smoke appear to have more unsaturated and less oxygenated components than those observed in mainstream smoke (16), and sidestream smoke is inhaled mainly by passive smokers. Our study confirmed the previously established association between ETS and lung cancer (17); the OR for risk associated with lung cancer for subjects who have been exposed for 15 yr or more compared to no exposure to ETS was 2.60 (95% CI: 1.69-3.99), higher than pooled RR for never-smoking women exposed to passive smoking from spouses (RR = 1.27, 95% CI: 1.17-1.37) of the metaanalysis Downloaded by [University of Nebraska, Lincoln] at 10:24 13 October 2014 conducted by Taylor et al (18).…”
Section: Discussionmentioning
confidence: 99%
“…Cigarettes are an ubiquitous form of tobacco use and a large number of chemical reactions take place when a cigarette is burned� Cigarette smoke is an aerosol that is primarily composed of extremely fine liquid droplets suspended in a complex gaseous system (Rodgman & Perfetti, 2009)� Two kinds of smoke with some differences in their composition and properties are produced during smoking: (i) mainstream smoke that is directly inhaled by the smoker and (ii) sidestream smoke, which is released into the environment between puffs from the lit end of the cigarette (Thielen et al�, 2008)� According to the American Lung Association, cigarette smoke contains over 4800 identified chemicals� Besides nitrogen and oxygen, major components in cigarette smoke include carbon dioxide, carbon monoxide, methane, and nicotine, with lesser but still substantial amounts of acetone, acetylene, formaldehyde, propane, hydrogen cyanide and toluene� Table 1 provides a more detailed (but not exhaustive) accounting of compounds found in mainstream cigarette smoke� Secondhand tobacco smoke consists of exhaled mainstream smoke as well as sidestream smoke that is released from the burning cigarette between inhalations (Schramm et al�, 2011)� Secondhand tobacco smoke also is referred to as 'environmental' tobacco smoke (WHO, 2002)� The composition of secondhand smoke changes as it becomes diluted with ambient air, with its distribution in the environment and as it interacts over time with compounds found in the environment� However, no matter how secondhand smoke changes in the environment, it still contains significant levels of nicotine� Nicotine concentrations in the air in homes of smokers range on average from 2 to 10 µg/m 3 (WHO, 2002)� When sidestream cigarette smoke is compared to mainstream smoke, the types of compounds present show qualitative similarities� However, some quantitative differences have been noted� A significant number of compounds are increased in sidestream cigarette smoke compared to mainstream smoke, including (but not limited to) ammonia, cadmium, chromium, lead, nickel, isoprene, benzene, …”
Section: Introductionmentioning
confidence: 99%